THE EFFECT OF THE PRESENCE OF FOREIGN BOARD MEMBERS ON CORPORATE ESG SCORES IN INDONESIA - Reynald Emmanuel Dwistia; Kanisius Kevin Widjaja; Meythi Meythi; Riki Martusa (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to examine the impact of foreign boards and board commissioners on ESG scores in Indonesia from 2019-2023. Drawing upon the resource dependency theory, this paper applies multiple linear regression to investigate whether foreign boards and ESG performance of firms listed on Indonesia Stock Exchange (IDX) are related. The results indicate that foreign boards presence impacts ESG scores positively at 10%. Although this highlights that oversea boards can have a positive impact in such ways through expertise and global connections, the regulatory setting will remain just as important even if it is under reform. Instead, foreign boards have an insignificant negative impact on the ESG scores both for overall governance and all sub-dimensions suggesting that it may not be appropriate to use a more diversified board in terms of origin as panacea especially when it comes to advancing ESG practices. This study also has several limitations in that it explored companies from Indonesia, the period of research took place in a limited time frame and board demographics were not considered. Based on this study, one may argue part of the solution is to rely more heavily on foreign boards with greater familiarity and experience in implementing ESG appropriately for local conditions. The results are expected to provide implications for firms and regulators about the significance of board composition which enhances ESG performance, and corporate sustainability.